The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00113-012-2294-9
|View full text |Cite
|
Sign up to set email alerts
|

Anterosuperiore Rotatorenmanschettenrupturen

Abstract: Due to convincing short-term clinical results and advantages of minimally invasive surgery, arthroscopic treatment of anterior and anterosuperior rotator cuff tears has become prevalent. Treatment of concomitant LBS tendon pathology seems to play an important role in most patients. Further development of refixation techniques and better means of visualization will increase the trend towards arthroscopic treatment of anterosuperior rotator cuff tears in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Anterior and anterosuperior cuff tears have gained more attention in the past years [2,8,[20][21][22]. Since the subscapularis tendon is the anterior part of the transversal ''force couple'', it is important for a satisfactory shoulder function [4].…”
Section: Discussionmentioning
confidence: 99%
“…Anterior and anterosuperior cuff tears have gained more attention in the past years [2,8,[20][21][22]. Since the subscapularis tendon is the anterior part of the transversal ''force couple'', it is important for a satisfactory shoulder function [4].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [33] showed similar 24-month postoperative outcomes in 35 patients with a massive posterosuperior RC tear and associated partial SSC tendon tear treated with debridement only compared to that for patients with an intact SSC. Katthagen et al [28] reported on 25 patients with anterosuperior cuf tears and a debrided Lafosse I SSC tear who improved in both function and level of pain. The non-repair group of the current work presented has similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature reporting on the treatment of partial SSC tendon tears has mostly included either small patient numbers or a heterogeneous patient collective with variable outcomes [19, 28–30, 33, 39]. Kim et al [30] demonstrated improved shoulder function in a series of 29 patients each with a repaired isolated, articular‐sided partial cranial SSC tendon tear of at least 5 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This period is often missed, and later larger lesions need more invasive surgical procedures. It is known that most arthroscopic techniques are an alternative type of Bankarts' capsuloplasties that are successful in cases of physiological predisposition, bone lesions of the glenoidal edge, rotator cuff lesions and Hill-Sachs lesions -up to 15%-20% [6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%